Plasma and Urine Neutrophil Gelatinase–Associated Lipocalin (NGAL) in Dogs with Acute Kidney Injury or Chronic Kidney Disease. (13th January 2014) - Steinbach, S.; Weis, J.; Schweighauser, A.; Francey, T.; Neiger, R.
<x xml:space="preserve">Abstract</x> Background Neutrophil gelatinase–associated lipocalin (NGAL) is a protein that is used in human medicine as a real‐time indicator of acute kidney injury (AKI). Hypothesis Dogs with AKI have significantly higher plasma NGAL concentration and urine NGAL‐to‐creatinine ratio (UNCR) compared with healthy dogs and dogs with chronic kidney disease (CKD). Animals 18 healthy control dogs, 17 dogs with CKD, and 48 dogs with AKI. Methods Over a period of 1 year, all dogs with renal azotemia were prospectively included. Urine and plasma samples were collected during the first 24 hours after presentation or after development of renal azotemia. Plasma and urine NGAL concentrations were measured with a commercially available canine NGAL Elisa Kit (Bioporto® Diagnostic) and UNCR was calculated. A single‐injection plasma inulin clearance was performed in the healthy dogs. Results Median (range) NGAL plasma concentration in healthy dogs, dogs with CKD, and AKI were 10.7 ng/mL (2.5–21.2), 22.0 ng/mL (7.7–62.3), and 48.3 ng/mL (5.7–469.0), respectively. UNCR was 2 × 10−8 (0–46), 1, 424 × 10−8 (385–18, 347), and 2, 366 × 10−8 (36–994, 669), respectively. Dogs with renal azotemia had significantly higher NGAL concentrations and UNCR than did healthy dogs (P < .0001 for both). Plasma NGAL concentration was significantly higher in dogs with AKI compared with dogs with CKD (P = .027). Conclusions and Clinical Importance Plasma NGAL could be helpful to differentiate AKI from CKD in dogs with renal azotemia.